2020
DOI: 10.1038/s41419-020-2436-x
|View full text |Cite
|
Sign up to set email alerts
|

YIPF2 promotes chemotherapeutic agent-mediated apoptosis via enhancing TNFRSF10B recycling to plasma membrane in non-small cell lung cancer cells

Abstract: Non-small cell lung cancer (NSCLC) is the most common histological type of lung cancer, and the identification of the apoptotic process of NSCLC is vital for its treatment. Usually, both the expression level and the cell surface level of TNFRSF10B (TNF Receptor superfamily member 10B) will increase after treatment with some chemotherapeutic agents, which plays a critical role in the apoptosis induction. However, the exact molecular mechanism underlying TNFRSF10B regulation remains largely elusive. Here, we fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…As a result, eight genes (TNFRSF10B, LTBR, TNFRSF10C, TNFSF11, TNFRSF19, NGFR, TNFRSF11A, and TNFRSF25) were used to establish the TFS. TNFRSF10B (also known as DR5 or TRAILR2) is a protein that belongs to the TNFRSF family and mediates the extrinsic apoptotic pathway in various cancer cells [27]. Recent studies revealed that upregulation of this protein in human CRC cells enhanced the efficiency of cancer therapy [28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…As a result, eight genes (TNFRSF10B, LTBR, TNFRSF10C, TNFSF11, TNFRSF19, NGFR, TNFRSF11A, and TNFRSF25) were used to establish the TFS. TNFRSF10B (also known as DR5 or TRAILR2) is a protein that belongs to the TNFRSF family and mediates the extrinsic apoptotic pathway in various cancer cells [27]. Recent studies revealed that upregulation of this protein in human CRC cells enhanced the efficiency of cancer therapy [28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…YIPF2 facilitated chemotherapeutic drug-mediated apoptosis by promoting TNFRSF10B cell membrane circulation in NSCLC. 66 ASTX660 as a cIAP1/2 and X-linked inhibitor of apoptosis protein (XIAP) antagonist could sensitize murine oral cancer (MOC1) cells to TNF-α and induce apoptosis of TNFR superfamily downstream cells. Besides, ASTX660 combined with cisplatin and PD-1 blockade could delay tumor growth.…”
Section: Crucial Signaling Pathways Of Rcd Subroutines In Cancermentioning
confidence: 99%
“…In NSCLC tissues, CircRNF20 aggravates the progression of non-small cell lung cancer by activating MAPK9 [37]. YIPF2 can enhance the recirculation of TNFRSF10B to the plasma membrane in non-small cell lung cancer cells, thus promote chemotherapeutic-mediated apoptosis [38]. The reports of these genes in LGG are not complete, and further analysis is needed to explore their effects.…”
Section: Discussionmentioning
confidence: 99%